What do adults with visual impairment mean by well-being? Identifying the building blocks of well-being in the context of visual impairment - Heinze, Nikki; Davies, Ffion; York, Sarah; Chan, Stephanie Hoi-Ying; Farrell, Derek; Gomes, Renata S. M. (Frontiers in Psychology, 2024)
This article summarises findings from a series of focus groups which explored what adults with visual impairment (V.I.) and V.I. practitioners mean when they talk about well-being. As such, it contributes to the topic area of 'well-being' within the Health Psychology subsection of Frontiers in Psychology. This research builds on findings from a scoping review of academic literature, published in Frontiers in Psychology, which showed the lack of consensus in how well-being has been conceptualized in V.I. research, if indeed it has been defined at all. A shared understanding of what well-being means, and how it should be assessed, is essential to ensure not only the comparability and replicability of research findings, but, crucially, to enable collaboration between V.I. support organisations. The article describes the building blocks of well-being identified by participants, including its components, factors that impact it, and a protective buffer which may mitigate the impact of factors. Although the findings need to be confirmed, the article goes on to propose a model of well-being which aims to be practical and intuitive. Using a bottom-up approach, it reflects the individual elements and structure identified by participants, as well as the subjective nature of wellbeing highlighted by many.